P68 Outcome of a Pragmatic Protocol For CT Lung Nodule Surveillance in a UK District General Hospital. (19th November 2012) - Reichmann, MT; Edwards, D; Sivaloganathan, A; Drury, A; Laws, D
Abstract : Introduction and objectives: The appropriate way to follow-up indeterminate pulmonary nodules found incidentally on CT scanning has caused clinicians and radiologists in the UK some concern. Guidelines developed by the Fleischner Society in 2005 were based on studies outside of the UK. Our hospital developed local guidance for lung nodule surveillance prior to the publication of Fleischner guidelines which were designed to be pragmatic and easy to follow. We present the results of our experience. Methods: Outcomes of patients undergoing the local lung nodule surveillance programme in our hospital from 2004 to 2011 were analysed. Eligibility criteria included initial lung nodules 5–10mm diameter; previous or current smokers; aged 45–75 years old with good performance status. Those with 5 or more nodules more than 5mm diameter, benign calcification, or patients already under follow up, e.g. oncology patients, were excluded. A stamp was placed in the notes and on CT request forms to record and remind clinicians of the criteria. In accordance to our protocol CT scans were performed at 6, 18 and 30 months from the index scan. Results: 107 patients were followed up but only 63 patients fulfilled the initial inclusion criteria. This shows that despite a pragmatic protocol, clinicians will often interpret it differently when faced with an individual. The commonest reason was nodule size over 10mm. Of those eligible, the outcomes were recorded as to whether nodule confirmed as cancer (positive), nodule size reduced or unchanged over 30 months (negative), surveillance cut short as a clinical decision and those still under surveillance. Of the 63 patients, 2 were found to have lung cancer (see Figure 1 ). Of those patients who were not eligible, but still underwent the surveillance programme, 6 were found to have cancer. These were not eligible because nodule size was over 10mm. Conclusions: Our study shows that a simple protocol is helpful to clinicians, but will be adapted according to the clinicians' belief. In our study 3% of nodules 5–10mm were early cancers. Nodules over 10mm, which were bigger than our criteria but followed up within this protocol, were more likely to be cancerous (14%).